Calculating the feature method of short text based on analytic hierarchy process - Xue-qiang ZOU; Xiu-guo BAO; Xiao-jun HUANG; Hong-yuan MA; Qing-sheng YUAN (Tongxin xuebao)
In order to model the accurate interest preference of microblog users and discover user groups with similar in-terest, a new method was proposed which considered the total amount of retweets, comments and attitudes of each mi-croblog for text feature calculation with utilizing classic analytical hierarchy process method. The proposed method used three indicators to evaluate the importance of the text feature representation and made an improvement on traditional tf-idf feature calculation method to fit for short text. Furthermore, this method was also implemented in the traditional clustering algorithm. Experimental results show that, compared with the traditional tf-idf method, the improved approach has a better clustering effect on the average scattering for clusters and the total separation between clusters.